Identification of key individuals and groups for effecting policy change and establish ToR's for the taskforce / working group - Jennings, Stewart (2023)
A working group of stakeholders has been created to aid in shaping results and result dissemination for effecting policy change in Zambia. A first meeting was held in Lusaka on March 7th to present iFEED to the working group and begin discussions about how to use results to inform policy development. Further meetings took place in Q2 2023 between Leeds WP3 and the working group to finalise these results and how they will be used to inform policy change.